1)Ca + 2H2O = Ca(OH)2 + H2
Ca -2e = Ca(2+) / 2 / 1 - окисление , восстановитель
2H(+) +2e = H2 / 2 / 1 - восстановление , окислитель
2)Ca(OH)2 + CO2 = CaCO3 + H2O - молекулярное уравнение
Ca(2+) + 2OH(-) + CO2 = CaCO3 + H2O - ионное полное уравнение
3)Fe(OH)3 + 3HCl + 3H2O = (Fe(H2O)6)Cl3
Объяснение:
1)Ca + 2H2O = Ca(OH)2 + H2
Ca -2e = Ca(2+) / 2 / 1 - окисление , восстановитель
2H(+) +2e = H2 / 2 / 1 - восстановление , окислитель
2)Ca(OH)2 + CO2 = CaCO3 + H2O - молекулярное уравнение
Ca(2+) + 2OH(-) + CO2 = CaCO3 + H2O - ионное полное уравнение
3)Fe(OH)3 + 3HCl + 3H2O = (Fe(H2O)6)Cl3
Объяснение: